HUBUNGAN ANTARA PERSONAL PREFERENCE DALAM PENERAPAN POLA MAKAN DENGAN KEJADIAN GASTRITIS PADA MAHASISWA STIKES YARSIS - Wijayanti, Lono; Rosyidah, Hikmah (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2013)
The wrong application of eating pattern in daily life may result in the incidence of gastritis. Most student who have negative response with personal preference in application of eating pattern more risk of gastritis happen. Therefore, the purpose of this research was to find out the relationship between the personal preference in applying the eating pattern and gastritis incidence happening in the students of Stikes Yarsis. The design of research was analytic-cross sectional. The population involved all students of Stikes Yarsis in the last semester, totally 423 students, in which 139 students were taken as the samples done by applying the probability sampling, with the stratified random sampling technique. The personal preference in applying the eating pattern was chosen as the independent variable, whereas the dependent variable was the incidence of gastritis. Furthermore, questionnaires were used to collect the data. The result of research showed that nearly all of the respondents (73.4%) had a positive response on the personal preference in applying the eating pattern, whereas most of them (66.9%) suffered from gastritis. The analysis of Chi-Square test showed that ρ = 0.019 < α = 0.05 so that H0 was rejected illustrating that there was a relationship between the personal preference in applying the eating pattern and the incidence of gastritis. In conclusion, the more negative response to personal preference, the more gastritis happen and the more positive response to personal preference can also gastritis happen. Therefore, the motivation and self awareness to prevent hot and acid food to apply the good eating pattern so that gastritis happen can be prevented.